THE EFFECT OF HEALTH EDUCATION WITH BOOKLET MEDIA ON THE KNOWLEDGE OF FEMALE TEENS ABOUT BSE IN STUDENTS OF JUNIOR HIGH SCHOOL 4 KOTA PARIAMAN. - PRASETYANINGSIH; YUNTARISA, ATIKA PRADANA; ZALMADANI, HENDRO (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2025)
Breast cancer cases have threatened life safety. In Indonesia, out of 396,914 sufferers, there have been 22,000 deaths. The cause is due to delays in detection so that when symptoms appear, they have entered the final stage, namely death. The purpose of the study was to determine the effect of health education with booklet media on the knowledge of female adolescents about BSE in students of SMPN 4 Pariaman. The type of research is quantitative with a quasi-experimental design with a one group pretest posttest approach. The population in the study were 82 students of class VIII of SMP 4 Pariaman. The research sample was 17 students of class VIII of SMP 4 Pariaman who had menstruated. The sampling technique was purposive sampling. Data analysis was carried out using a paired t-test at the 5% level. The results of the study showed that most respondents before being given health education had low knowledge of 13 people (76.5%), and after being given health education, all respondents had high knowledge (100%). Paired t-analysis shows that the p-value = 0.000 <α = 0.05. It can be concluded that there is an influence of health education with booklet media on the knowledge of female adolescents about BSE in SMPN 4 Pariaman students. Suggestion, it is expected that all female students can practice the movements and procedures in the BSE examination in the booklet media periodically.